Children, education and armed conflict: an analysis of the African reality seen 15 years after the Machel Report - Óscar Mateos Martín (FahrenHouse, 2012)
While sub-Saharan Africa in recent years has faced a marked decline in the number of armed conflicts, a number of countries continue to suffer the consequences of organized violence, especially some contexts such as the Democratic Republic of Congo, the Darfur region (western Sudan) and Somalia, to name a few. As some institutions (UN or NGO) or lead scholars have highlighted for several years, the main victim of violence is often civilians, mainly children and women. This article aims to analyze the impact of armed conflicts in Africa have in childhood and in such important areas as education. This object of study has in recent years an important reference as it has been the publication in 1996 of the so-called "Machel Report". Fifteen years after the appearance of this document is of interest to a do a brief balance of some of the progress, gaps and main challenges of protecting children in armed conflict.